2021
DOI: 10.1186/s12885-021-08458-4
|View full text |Cite
|
Sign up to set email alerts
|

Pretreatment systemic inflammation response index is predictive of pathological complete response in patients with breast cancer receiving neoadjuvant chemotherapy

Abstract: Background Inflammation plays an important role in tumor proliferation, metastasis, and resistance to chemotherapy. The systemic inflammation response index (SIRI), has been reported to be closely related to prognosis in many tumors, such as breast and gastric cancers. However, the predictive value of pretreatment SIRI on pathological complete response (pCR) rates in patients with breast cancer treated with neoadjuvant chemotherapy (NAC) is unknown. This study examined the correlation between S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 31 publications
(36 reference statements)
0
19
0
Order By: Relevance
“…However, patients who had HR-negative status were more likely to achieve bpCR compared with those who had HR-positive status (76.2% vs. 48.3%, p = 0.047). Prior findings discovered that patients with high Ki-67 level, small tumor size, or low clinical stage have better access to get pCR (33)(34)(35). Due to the limited sample size, this study failed to co nfi r m t he c o r r e l a t i o n b e t w e e n tp C R a n d o t he r clinicopathological indicators.…”
Section: Discussionmentioning
confidence: 79%
“…However, patients who had HR-negative status were more likely to achieve bpCR compared with those who had HR-positive status (76.2% vs. 48.3%, p = 0.047). Prior findings discovered that patients with high Ki-67 level, small tumor size, or low clinical stage have better access to get pCR (33)(34)(35). Due to the limited sample size, this study failed to co nfi r m t he c o r r e l a t i o n b e t w e e n tp C R a n d o t he r clinicopathological indicators.…”
Section: Discussionmentioning
confidence: 79%
“…Certain studies have affirmed the validity of a systemic immune-inflammation index in predicting pathological response and patient prognosis after NCT for breast cancer (19,20). Powell et al (21) have also reported an association between low pretreatment NLRs and good pathological responses in patients with esophageal cancer, and Caputo et al (22) have documented both poorer TRG and increased incidence of postoperative complications in patients with rectal cancers and high preoperative NLRs.…”
Section: Discussionmentioning
confidence: 99%
“…Certain studies have affirmed the validity of a systemic immune-inflammation index in predicting pathological response and patient prognosis after NCT for breast cancer ( 19 , 20 ). Powell et al.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have confirmed that various markers of the systemic inflammatory response, for example, the C-reactive Protein (CRP), Platelet to Lymphocyte Ratio (PLR), Lymphocyte to Monocyte Ratio (LMR), and Neutrophil to Lymphocyte Ratio (NLR), all correlate to the prognosis of a myriad of tumors such as high-grade glioma ( He et al, 2021b ), colorectal cancer ( Dagmura et al, 2021 ), head and neck cancer ( Saroul et al, 2021 ), oral squamous cell cancer ( Yamagata et al, 2021 ), and gastric cancer ( Liu et al, 2021 ). The latest evidence also suggests that a similar tumor-inflammation relationship exists for breast cancer, indicating that quantifying the inflammatory response may be useful in treating and prognosticating breast cancer ( Dong et al, 2021 ). Common blood indices, including platelets (P), monocytes (M), neutrophils (N), hemoglobin (Hb), total red blood cell count (R), total white blood cell count (WBC), and serum albumin (ALB), along with its derivatives, NLR, MLR, LMR, PLR, D-NLR, prognostic nutritional value [PNI, 10 × serum ALB (g/dL) + 0.005 × total lymphocyte count], and SIRI (Neutrophil × Platelet/Lymphocyte) may all be reflective of malignant tumor states ( Mantovani et al, 2008 ).…”
Section: Introductionmentioning
confidence: 98%